Metta Meditation - Kumari, Nisha; Damodaran, Yadu K; Sharma, Mukesh (Journal of Mental Health and Social Rehabilitation, 2023)
Meditation is a transformative journey that begins with self-compassion and extends to encompass all beings. Through this article, a comprehensive guide, we will try explore the historical roots, core principles, psychological foundations, and practical applications of Metta Meditation, emphasizing its profound impact on cultivating self-compassion. This requires a commitment to regular practice. As the conclusion part, we reported how to navigate the complexities of modern life, the ancient wisdom of Metta Meditation beckons us to embrace the transformative power of self-love and compassion.